Preference for Long-Acting HIV Prevention Methods Among Transgender Women Vulnerable to HIV in Eastern and Southern United States: Findings from the LITE Study. - Cooney, Erin E.; Stevenson, Meg; Aguayo-Romero, Rodrigo A.; Valera, Genesis; Poteat, Tonia C.; Mayer, Kenneth H.; Beyrer, Chris; Althoff, Keri N.; Radix, Asa E.; Wawrzyniak, Andrew J.; Cannon, Christopher M.; Schneider, Jason S.; et al. (AIDS & Behavior, 2025)
HIV incidence among transgender women remains high and disproportionately impacts young, Black, and Latina transgender women. Data on preferred PrEP modalities among this population are limited. Participants in The LITE Cohort completed a survey module on PrEP modality preferences during 24-month study visits. We summarized ranked preferences based on an exhaustive set of 10 head-to-head comparisons of 5 PrEP modalities (pill, injection, implantable device, topical gel, and intravenous antibodies) and conducted in-depth interviews to contextualize findings. Between 2020 and 2022, 789 participants completed the PrEP modality survey module. The most preferred PrEP modality was the implant (ranked first among 45% of respondents), followed by pill (21%), injection (19%), gel (10%), and intravenous antibodies (4%). The implant ranked highest among Latina transgender women (36%), young adult transgender women (ages 18–24 years; 41%), those living in the South (47%), and those with PrEP indication(s) (45%), while injection was the top-ranked modality among Black transgender women (30%). Qualitative analysis of in-depth interviews (n = 45) revealed that PrEP modality preferences were individualized, context-dependent, considered gender-related factors (e.g. gender-affirming hormone injections), and informed by prior healthcare experiences, personal values, and anticipated modality-specific facilitators and barriers. Our findings suggest high interest in long-acting PrEP options, including implants and injections, and daily pills among transgender women.